2003
DOI: 10.1086/379513
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Isoniazid Treatment for Latent Tuberculosis Infection among Human Immunodeficiency Virus (HIV)-Infected and HIV-Uninfected Injection Drug Users in Methadone Programs

Abstract: Injection drug users (IDUs) were heavily affected by the tuberculosis (TB) resurgence in New York City in the 1990s. We assessed the effectiveness of screening for latent TB infection in methadone users and of selective treatment with isoniazid. Risk for future TB was classified as low or high on the basis of tuberculin, anergy, and HIV test results. The cohort of 2212 IDUs was followed up for a median of 4.2 years; 25 IDUs, of whom 20 (80%) were infected with human immunodeficiency virus (HIV), developed TB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
(21 reference statements)
0
25
0
1
Order By: Relevance
“…18,19 Moreover, there are several examples of where colocation of multiple services, particularly for drug users, has resulted in improved health outcomes. [20][21][22] The high rate at which these services were utilized in this study is not surprising, because HIV-infected drug users are known to have high rates of emergency room use 23 as well as multiple medical 24 and psychiatric comorbidities 25 and many preventive health care needs. 26,27 This study is the first to demonstrate an improved HIV-specific therapeutic improvement associated with such on-site service use.…”
Section: Discussionmentioning
confidence: 90%
“…18,19 Moreover, there are several examples of where colocation of multiple services, particularly for drug users, has resulted in improved health outcomes. [20][21][22] The high rate at which these services were utilized in this study is not surprising, because HIV-infected drug users are known to have high rates of emergency room use 23 as well as multiple medical 24 and psychiatric comorbidities 25 and many preventive health care needs. 26,27 This study is the first to demonstrate an improved HIV-specific therapeutic improvement associated with such on-site service use.…”
Section: Discussionmentioning
confidence: 90%
“…29 A study in New York, New York, demonstrated a reduction in TB among methadone users after they were targeted for LTBI screening and treatment. 30 Nonetheless, the TB/HIV comorbidity rate in this group remains high (44% in 2003), suggesting the need for additional and continued control efforts. The decrease in the number of TB/HIV cases among the homeless is related to the overall decrease in the number of homeless people with TB.…”
Section: Commentmentioning
confidence: 97%
“…Additionally, individuals who use illicit substances, particularly opioids, are at increased age-matched risk for associated infectious diseases such as tuberculosis (TB) (3)(4)(5), HIV (6,7), and viral hepatitis (8,9). Such disparity is in part due to, as well as aggravated by, a significant marginalization from mainstream healthcare resources (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there is a significant need for increased drug treatment accompanied by linkage to primary care services to address such co-morbidities in this population (12). Some programs have begun to respond by integrating primary care services with substance abuse treatment (13)(14)(15)(16), including screening and treatment of diseases commonly affecting substance users (4,5,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation